2020
DOI: 10.1111/ajgw.12454
|View full text |Cite
|
Sign up to set email alerts
|

Oenological characteristics of Vitis vinifera L. Cabernet Sauvignon grapes from vineyards treated with ozonated water

Abstract: Background and Aims Ozonated water has been used in vineyards to reduce the use of pesticides because of its presumed efficacy in the control of fungal diseases and the absence of residues. The aim of this study was to evaluate the effect of ozonated water treatments on the composition of grapes. Methods and Results Ozonated water was applied to grapevines of Vitis vinifera cv. Cabernet Sauvignon throughout the season. Several application strategies were used, namely, spraying, irrigation, irrigation combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Besides, the role of ozone in preventing or controlling infections of Plasmopara viticola and Erysiphe necator , the agents responsible for downy and powdery mildews in grapevine, has not yet been confirmed. Previous field experiments reported versatile impacts of ozonated water sprayings on the composition in phenolic and terpenoid compounds of grapes and resulting wines 12 14 , 16 . Such discrepancies suggest that more studies in controlled conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the role of ozone in preventing or controlling infections of Plasmopara viticola and Erysiphe necator , the agents responsible for downy and powdery mildews in grapevine, has not yet been confirmed. Previous field experiments reported versatile impacts of ozonated water sprayings on the composition in phenolic and terpenoid compounds of grapes and resulting wines 12 14 , 16 . Such discrepancies suggest that more studies in controlled conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, ozone applied in aqueous solution and in a timely manner is expected to interact with plants differently than in the gaseous state, with a sufficiently high phytotoxic threshold that allows its incorporation in irrigation and spraying treatments in different crop species 11 . Unfortunately, literature concerning the effects of ozonated water on grapevine plants is scarce and almost exclusively dedicated to analysing its effect on microbial populations 3 , 4 , 12 , except a few recent studies describing its impact on grape and wine composition 12 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the major use of ozone in agriculture lies in its antifungal activities, as con rmed in grapevine 1,2,10 , there is still a lack of information on how ozone can affect grapevine physiology and grape composition. Previous eld studies reported versatile impacts of ozonated water sprayings on the composition of grapes and resulting wines, with phenolic and terpenoid compounds increased or decreased by ozone without showing a linear correlation with the number of applications [10][11][12]14 . Such heterogeneous results indicate that more studies in controlled conditions are needed to understand the molecular and biochemical changes induced by O 3 in grapevine organs.…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, literature concerning the effects of ozonated water on grapevine plants is scarce and almost exclusively dedicated to analysing its effect on microbial populations 1,2,10 , except a few recent studies describing its impact on grape and wine composition [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…The use of ozone (O 3 ) in the food industry has become widespread as it acts primarily as a disinfectant against a variety of microorganisms but also as a means of shelf-life extension of many foods. Meat [134,135], poultry [136], eggs [137], seafood [138], fruits [139,140], vegetables [141][142][143][144][145], juices [146], spices and herbs [147,148], dairy and dairy products [149], and dry foods have been treated with ozone for different purposes, among them sanitization and disinfection purposes [150,151]. Ozone as a non-thermal treatment has great antioxidant activity against bacteria, fungi, viruses, protozoa, and vegetative cells [152,153].…”
Section: Ozonationmentioning
confidence: 99%